Cortical Organization of Language Pathways in Children with Non-Localized Cryptogenic Epilepsy - Frye, Richard Eugene; Liederman, Jacqueline (Frontiers in Human Neuroscience, 2014)
Children with a history of epilepsy are almost six-times more likely than their unaffected siblings to be referred for speech or language therapy. However, the abnormalities in neural pathway that cause these delays are poorly understood. We recorded evoked fields using whole-head magnetoencephalography during real and non-word visual and auditory rhyme tasks in 15 children with non-localized cryptogenic epilepsy. Basic phonological and orthographic language skills were assessed using Woodcock-Johnson Test of Achievement subtests. Dynamic statistical parameter mapping was used with individual participant magnetic resonance images. Significant cortical activity was visualized on average and performance weighted maps. For the auditory rhyme tasks, bilateral primary and secondary auditory cortices, the superior temporal sulcus and insular cortex were activated early with later increases in left hemisphere activity. Visual rhyme tasks evoked early bilateral primary and secondary occipital cortical and angular gyri activity followed by later activation of the planum temporale and supramarginal gyri and the left ventral occipitotemporal area. For the auditory rhyme tasks, performance weighted maps demonstrated that early right hemisphere activation was associated with poorer reading skills while later activity was associated with better reading skills; for the left hemisphere, greater early activation of the secondary auditory cortex, including the planum temporale, was related to better reading skills while relatively later activation of these areas was associated with poorer reading skills. For the visual rhyme tasks, greater activity in the bilateral ventral occipitotemporal and insular areas and angular and supramarginal gyri were associated with better performance. These data suggest that spatiotemporal cortical activation patterns are associated with variations in language performance in non-localized cryptogenic epilepsy.